Effects of type of packaging material on physicochemical and sensory properties of olive oil - Rababah, Taha; Hao, Feng; Yang, Wade; Eriefej, Khalil; Al-Omoush, Mohamad (International Journal of Agricultural and Biological Engineering, 2012)
This study was performed to evaluate changes in physicochemical and sensory attributes of olive oil stored in different packaging materials for up to 60 days. ?The olive oil samples from a local company (Ajlon-Jordan) were stored in containers made from glass, tinplate, and plastic for two months at 25